Rutin exhibits an anti-resorptive effect in a medaka fish model of osteoporosis - Thuy, To Thanh; Diep, Nguyen Thi Bich; Anh, Nguyen Tuong; Manh, Nguyen Huy; Thuong, Phuong Thien (Vietnam Journal of Science and Technology, 2025)
With the increasing prevalence of osteoporosis worldwide due to an aging population, there is a substantial need for the search and development of new anti-osteoporosis substances. Rutin (quercetin-3-O-rhamnosyl glucoside) is a flavonoid glycoside found in many plants and herbal medicines, known for its potent antioxidant and potential osteoprotective properties. In this study we investigated the anti-osteoporotic effects of rutin, for the first time, using a medaka fish (Oryzias latipes) model for osteoporosis. The medaka fish model is a non-mammalian model that is increasingly preferred for drug screening. RANKL-induced osteoporosis fish larvae were treated with rutin at five different doses (10, 25, 50, 100, and 200 µM) for 96 hours starting from 7 days post-fertilization (dpf). The effect of rutin on bone damage was assessed via indexes of mineralization protection (IP) which are based on the index of bone mineralization (IM) of the tested fish. The results showed that rutin significantly reduced the level of RANKL-induced bone damage at concentrations of 10, 25, 50, and 100 µM, with the highest effect observed at a concentration of 10 µM. These findings provide important evidence for further studies on the bone-protective effects of rutin on medaka fish models for the development of anti-osteoporosis drugs.